(untitled) (IJOVTECH, 2026)
Distrust in political institutions is a worldwide phenomenon that places a significant burden on democratic governance, contributes to political, ethnic, social, and personal division, and leaves a nation vulnerable to underdevelopment. The pattern is reprehensible in every region of the world. The role of political distrust in the growing political misinformation has not received much attention in the research literature, although researchers have identified several reasons for political misinformation. The current research investigates whether political distrust can be attributed to the proliferation of false information in southeast Nigeria. Three hundred and thirteen participants conveniently pooled from different locations in the southeast region of Nigeria, particularly Enugu and Ebonyi, completed a self-report measure of political distrust and misinformation. A linear regression analysis was performed on the data, and the result showed that political misinformation was statistically significantly predicted by political distrust. According to the study's findings, a significant contributory factor in the growing political misinformation could be attributed to political mistrust.